Women’s participation in the interwar Roma movement in Romania - PETRE MATEI (Romani Studies)
This article analyzes the involvement of women in the Roma emancipation movement in interwar Romania. It aims to clarify several issues, such as the particularities of their participation, what they wanted to achieve, the problems they were confronted with, and how they tried to respond to those challenges. After offering some background information on the organizations of Romanian women and their social work serving as inspiration sources and social capital, the article analyzes the statutory provisions of the main Roma organizations aimed at women and compares these with women’s effective involvement in the movement throughout the 1930s. Roma women’s activism did not exist outside the Roma movement, but developed strictly within it. At least in the first stage (1933–1934), in the organizations led by (the more modern) Calinic I. Popp Șerboianu and G.A. Lăzărescu, Roma women were perceived and presented both as a resource and as an interface of the Roma emancipation project. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0.